Pengembangan Instrumen Penilaian Portofolio untuk Menulis Teks Eksplanasi dalam Pembelajaran Bahasa Indonesia Kelas XI di SMAN 1 Pekanbaru - Lutfi, M.; Sukenti, Desi (UIR Press, 2024)
This research aims to analyze, interpret, and conclude the development of assessment instruments for the basic competence of writing explanatory texts in Indonesian language learning for 11th-grade students at SMA N 1 Pekanbaru. In developing the portfolio assessment instrument, the researcher used the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The population in this study is the community of Tembilahan Subdistrict, Indragiri Hilir Regency. The research results show that in writing main ideas in the general statement section, only three students received a score of 20 or very poor. Meanwhile, in writing main ideas in the series of explanations section, only five students received a score of 20 or very poor. In terms of writing main ideas in the interpretation section, a total of 11 students were unable to do so. Similarly, in writing sentences containing factual information, only five students were unable to do so, and eight students were unable to write sentences containing information based on the sequence of events. Overall, the portfolio assessment instrument developed in this study meets the criteria for validity and is suitable for implementation in Indonesian language learning at SMA N 1 Pekanbar0075.